2014
DOI: 10.1093/nar/gku554
|View full text |Cite
|
Sign up to set email alerts
|

Transition-state destabilization reveals how human DNA polymerase β proceeds across the chemically unstable lesion N7-methylguanine

Abstract: N7-Methyl-2′-deoxyguanosine (m7dG) is the predominant lesion formed by methylating agents. A systematic investigation on the effect of m7dG on DNA replication has been difficult due to the chemical instability of m7dG. To gain insights into the m7dG effect, we employed a 2′-fluorine-mediated transition-state destabilzation strategy. Specifically, we determined kinetic parameters for dCTP insertion opposite a chemically stable m7dG analogue, 2′-fluoro-m7dG (Fm7dG), by human DNA polymerase β (polβ) and solved th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 38 publications
0
51
0
Order By: Relevance
“…Third, the nascent base-pair binding pocket of polβ is highly sensitive to structural and electronic perturbations caused by nucleobase lesions, particularly alkylated lesions. For example, polβ incorporates dCTP opposite N7-methylguanine 300-fold less efficiently than opposite guanine [47]. In addition, although N7-methylguanine:T forms a Watson-Crick-like conformation in the absence of protein contact [48], polβ does not permit the formation of a Watson-Crick-like N7-methylguaine:T base pair at the insertion site and induces a staggered base-pair conformation [47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, the nascent base-pair binding pocket of polβ is highly sensitive to structural and electronic perturbations caused by nucleobase lesions, particularly alkylated lesions. For example, polβ incorporates dCTP opposite N7-methylguanine 300-fold less efficiently than opposite guanine [47]. In addition, although N7-methylguanine:T forms a Watson-Crick-like conformation in the absence of protein contact [48], polβ does not permit the formation of a Watson-Crick-like N7-methylguaine:T base pair at the insertion site and induces a staggered base-pair conformation [47].…”
Section: Discussionmentioning
confidence: 99%
“…For example, polβ incorporates dCTP opposite N7-methylguanine 300-fold less efficiently than opposite guanine [47]. In addition, although N7-methylguanine:T forms a Watson-Crick-like conformation in the absence of protein contact [48], polβ does not permit the formation of a Watson-Crick-like N7-methylguaine:T base pair at the insertion site and induces a staggered base-pair conformation [47]. The enzyme’s active site architecture appears to sense the steric and/or electronic perturbation of the N7-methylguanine moiety.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 Previous crystallographic studies using the chemically stable 2′-fluoro-m 7 dG analog in a DNA sequence, either in complex with E. coli DNA glycosylase AlkA 26 or human DNA polymerase β 27 revealed that this polymerase bypasses m 7 dG accurately and that the lesion forms a canonical Watson-Crick base pair with incoming dCTP.…”
mentioning
confidence: 99%
“…49 When N7mG adduct is at the templating position, polβ adopts a closed conformation, showing that small alkyl group at the N7 position of G minimally affect polβ conformation. The polβ’s conformational difference between the N7bnG:dCTP* and N7mG:dCTP* structures suggests that the steric bulkiness of N7-alkylG adducts may significantly affect the conformational reorganization of some DNA polymerases.…”
Section: Resultsmentioning
confidence: 97%
“…49 Diffraction data were collected at 100 K at the beamline 5.0.3 at the Advanced Light Source, Lawrence Berkeley National Laboratory. All diffraction data were processed using HKL2000.…”
Section: Methodsmentioning
confidence: 99%